Inhibitory Mechanism of Quercimeritrin as a Novel α-Glucosidase Selective Inhibitor - Fengyu Guo; Jie An; Minlong Wang; Weibo Zhang; Chong Chen; Xueying Mao; Siyuan Liu; Pengjie Wang; Fazheng Ren (Foods, 2023)
In this study, 12 flavonoid glycosides were selected based on virtual screening and the literature, and Quercimeritrin was selected as the best selective inhibitor of α-glucosidase through in vitro enzyme activity inhibition experiments. Its IC50 value for α-glucosidase was 79.88 µM, and its IC50 value for α-amylase >250 µM. As such, it could be used as a new selective inhibitor of α-glucosidase. The selective inhibition mechanism of Quercimeritrin on the two starch-digesting enzymes was further explored, and it was confirmed that Quercimeritrin had a strong binding affinity for α-glucosidase and occupied the binding pocket of α-glucosidase through non-covalent binding. Subsequently, animal experiments demonstrated that Quercimeritrin can effectively control postprandial blood glucose in vivo, with the same inhibitory effect as acarbose but without side effects. Our results, therefore, provide insights into how flavone aglycones can be used to effectively control the rate of digestion to improve postprandial blood glucose levels.